Development and controlling factors of shale lithofacies cycles in a continental rift basin: A case study of Es4u in the Boxing Subsag of Dongying Sag, Bohai Bay Basin, China - Fang, Zhengwei; Zhang, Liqiang; Ma, Cunfei (Frontiers in Earth Science, 2023)
The shale of the upper submember of the fourth member of Eocene Shahejie Formation (Es4u) in the Boxing Subsag of the Dongying Sag, the Bohai Bay Basin, China, is a typical set of lime-rich shale in continental rift basin. Through logging data interpretation, core and thin section observations, and geochemical elements analysis, the development and controlling factors of lithofacies cycles of Es4u shale were analyzed. The results show that 22 types of marked lithofacies are developed in Es4u, indicating the sedimentary environments such as lower lakeshore slope zone, upper, middle and lower shallow-lake slope zones, semi-deep-lake zone, and deep-lake zone. Lithofacies cycles in three scales are recognized in Es4u: small-scale lithofacies cycles indicated by alternation of two lithofacies, meso-scale lithofacies cycles indicated by repetition of lithofacies associations or regular variation of multiple lithofacies, and large-scale lithofacies cycles indicated by regular variation of well logging curves, which have the average thickness of 0.4 m, 5 m and 35 m, respectively. According to the vertical variation of astronomical parameters and lithofacies cycles, it is found that the periodic change of long eccentricity is related to large-scale lithofacies cycle, the periodic change of slope is related to meso-scale lithofacies cycle, and the periodic change of precession is related to small-scale lithofacies cycle, while the periodic change of short eccentricity has poor correlation with lithofacies cycles. The climate change reflected by long eccentricity and slope is quite distinct from the actual basin climate reflected by the paleoclimatic parameters (e.g. Rb/Sr and Sr/Cu) obtained by X radial fluorescence mud logging (XRF), indicating that the basin paleoclimate was greatly influenced by the paleogeological conditions. For Es4u in the Boxing Subsag, about 55% of the stratigraphic record is dominantly controlled by the astronomical climate and 45% by the paleogeological conditions. Affected by the paleogeological conditions, large-scale and meso-scale lithofacies cycles are different in lithofacies types and superimposition patterns, and only small-scale lithofacies cycles are found repetitive vertically.